MENU

Solve the equation 4(1 - x) = 3(x + 1) - 2.

First, simplify each side to find the equivalent equation.

4 - 4x = 3x + 1

Step 3: Add 4x to each side to find that

4 = 7x + 1

and then subtract 1 from each side to find that 3 = 7x

We can conclude that $x = \frac{3}{7}$. We can also conclude that our lives are indeed easier now that we've kicked those parentheses to the curb.

Make it rain.

The who, what, where, when, and why of all your favorite quotes.

Go behind the scenes on all your favorite films.